FAKTOR YANG MEMPENGARUHI KEPUTUSAN UMKM SEKTOR PENGOLAHAN PANGAN UNTUK MENGAMBIL KREDIT TIDAK MENGAMBIL KREDIT DI KOTA YOGYAKARTA - ratih purbowisanti purbowisanti (Universitas Ahmad Dahlan, 2019)
This study aims to analyze the influence of financial literacy, gender, age, income level and length of business of the decision of SMEs in the food processing sector in Yogyakarta to take credit and not take credit. This study uses primary data obtained from 70 respondents 36 respondents who took credit and 34 respondents did not take credit and analyzed using logistic regression methods. The results showed partially independent variables in the form of financial literacy, gender, undergraduate education and income level had a significant effect on the dependent variable and the variables of age and business duration had no significant effect. Nagelkerke R Square value is 0.344 meaning that the financial literacy variable, gender, age, education level, income level and length of business can explain (the decision of SMEs to take credit is 34%. The remaining 66% is explained by other variables outside the model.